2011
DOI: 10.1002/smi.1395
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Relationship between Work Engagement and Symptoms of Anxiety and Depression

Abstract: This longitudinal study examined the dynamic relationship between work engagement (vigour and dedication) and symptoms of anxiety and depression. A sample of 3475 respondents from eight different occupational groups (lawyers, physicians, nurses, teachers, church ministers, bus drivers, people working in advertising and people working in information technology) in Norway supplied data at two points in time with a 2-year time interval. The advantages of longitudinal design were utilized, including testing of rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 46 publications
11
75
2
7
Order By: Relevance
“…The results are also in line with a study which claimed that engaged employees often experience positive emotions, including satisfaction with one's own life [13], but the results are not in line with the studies that claim that work-engaged employees have better physical health than others [10]- [12]. So why do the nurses perceive themselves to be of good health despite suffering from a number of ailments caused by prolonged strain at work?…”
Section: Discussionsupporting
confidence: 40%
“…The results are also in line with a study which claimed that engaged employees often experience positive emotions, including satisfaction with one's own life [13], but the results are not in line with the studies that claim that work-engaged employees have better physical health than others [10]- [12]. So why do the nurses perceive themselves to be of good health despite suffering from a number of ailments caused by prolonged strain at work?…”
Section: Discussionsupporting
confidence: 40%
“…A 7-year longitudinal study has demonstrated that the UWES scores negatively predict depressive symptoms and positively predict overall life satisfaction [26]. A 2-year longitudinal study on Norway employees has shown that vigor, one of the 3 dimensions of engagement measured by the UWES, is a negative predictor of depression symptoms and anxiety [27]. Furthermore, the longitudinal study among telecom managers shows that work engagement predicts the frequency of absence due to illness but not the duration of sick leave [28].…”
Section: Three-factorial Model Of Work Engagementmentioning
confidence: 99%
“…Badania dotyczące zdrowia psychosomatycznego wykazały, że bardziej zaangażo-wani pracownicy rzadziej odczuwają ból pleców i szyi [3] oraz mniej skarżą się na ból głowy, brzucha czy problemy z sercem [4]. Ponadto ujawniono, że wyższe zaangażowanie w pracę zmniejsza uczucie niepokoju i stresu u pracowników [5] oraz działa pozytywnie na ich zdrowie psychiczne podczas wykonywania obowiązków w pracy [6].…”
Section: Nr 2 278unclassified
“…Jednocześnie zaproponowali rozstrzygnięcia w zakresie terminologii w nadziei, że przyczynią się one do większej klarowności w przyszłych publikacjach z tego obszaru. Bez wątpienia jest to warte dalszych analiz, ponieważ sposób funkcjonowania w środowisku pracy ma istotne znaczenie dla zdrowia człowieka [3][4][5][6]. Przedstawione analizy mogą inspirować także do dopracowania polskich tłumaczeń innych terminów z obszaru medycyny i psychologii pracy, które niejednokrotnie stwarzają analogiczne problemy.…”
Section: Polskie Tłumaczenia Pojęć Z Koncepcji Schaufeliego I Bakkeraunclassified